2016
DOI: 10.1007/s40037-016-0301-5
|View full text |Cite
|
Sign up to set email alerts
|

Educating physicians in evidence based medicine: current practices and curricular strategies

Abstract: IntroductionEvidence-based medicine (EBM) is an expectation of professional healthcare and a requisite component of medical school curricula. However, upon graduation medical students’ EBM skills have been found lacking suggesting a need to examine EBM training.MethodsThis PhD report presents two studies on EBM education. The first study is a literature review that describes and attempts to assess educational interventions for teaching medical students EBM. The second study presents a multi-institutional case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 13 publications
1
25
0
1
Order By: Relevance
“…Clinical decision making is not uniform and opinions regarding the "proper" management may differ among clinicians; however, these various courses of actions need to be grounded in the best available evidence, acknowledge limitations in the evidence, and patients values and preferences. Role modeling has been shown to play an important role in transferring positive aspects of the hidden curriculum [41,42] and EBM skills [43]. Our results suggest that PowerPoint slides should be con-sidered as an additional medium to model EBM and SDM skills during day-to-day clinical didactic teaching.…”
Section: Discussionmentioning
confidence: 80%
“…Clinical decision making is not uniform and opinions regarding the "proper" management may differ among clinicians; however, these various courses of actions need to be grounded in the best available evidence, acknowledge limitations in the evidence, and patients values and preferences. Role modeling has been shown to play an important role in transferring positive aspects of the hidden curriculum [41,42] and EBM skills [43]. Our results suggest that PowerPoint slides should be con-sidered as an additional medium to model EBM and SDM skills during day-to-day clinical didactic teaching.…”
Section: Discussionmentioning
confidence: 80%
“…Among the 72 articles included in the review (see Appendix S1, online, for a full list), 10 papers reported findings from four overarching studies. These included three papers by Rodr ıguez et al, [15][16][17] one paper by L opez-Roig et al, 18 two papers by Van Hoof et al, 19,20 one paper by Maggio 21 and one by Maggio et al, 22 and two papers by Preston et al 23,24 The articles reviewed utilised a CSR approach for a diverse range of topics (Appendix S1).…”
Section: Resultsmentioning
confidence: 99%
“…According to the literature, teaching of EbM content can be successfully achieved in various settings (teacher-centred, e-learning, blended learning) [13,27,28]. In the present study, the resource was defi ned as an optional means for students' self-study.…”
Section: Discussionmentioning
confidence: 98%